PEMANTAUAN KONDISI HIDROLOGI DI PERAIRAN RAHA P. MUNA SULAWESI TENGGARA DALAM KAITANNYA DENGAN KONDISI TERUMBU KARANG - Edward, Edward; Tarigan, Z (UI Scholars Hub, 2003)
Monitoring On Hydrology Condition In Raha Waters Muna Island and Its Relation to Coral Reef Condition. Monitoring on hydrology condition in Raha waters Muna Island, Southeast of Sulawesi were carried out on May and June 2001. The results showed that the temperature vary between 27.80-30.39 oC, salinity between 30.0-32.9 ppt, suspended solid between 70-80 ppm, transparency between see bottom – 8,5 m, nutrient phosphate between 0.13-1.79 mg/l, nitrate between 0.20-2.66 mg/l, dissolved oxygen between 3,68-4.53 ppm, and pH between 7.4-8.2. The values are still good for coralreef growth and development, and still in good agreement with government criteria for miscellaneous purpose. The variation of hydrology condition is not the caution of coral reef damage in Raha waters.